Nitrogen-doped TiO2 microspheres with hierarchical micro/nanostructures and rich dual-phase junctions for enhanced photocatalytic activity. Issue 47 (25th April 2016) - Wang, Wei; Liu, Yu; Qu, Jifa; Chen, Yubo; Shao, Zongping
Abstract : We successfully synthesized microspherical nitrogen-doped TiO2 with hierarchical nano/microstructures, rich anatase TiO2 –TiO2 (B) phase junctions and a reduced band gap for the photo-degradation of dyes with improved photocatalytic activity. Abstract : We successfully synthesized microspherical nitrogen-doped TiO2 with hierarchical nano/microstructures, rich anatase TiO2 –TiO2 (B) phase junctions and a reduced band gap by a facile solvothermal process, followed by a urea-based solid-state reaction. Three kinds of nitrogen species in different doping sites, which can improve the photocatalytic activity and reduce the band gap, were found in the hierarchical nitrogen-doped TiO2 microspheres. In particular, a suitable amount of nitrogen doping was found to effectively reduce the Ti 3+ concentration in TiO2, thus benefiting the photocatalytic reaction by reducing the recombination centers in the photocatalyst. The combination of hierarchical microspherical morphology, the rich phase junctions and narrowed band gap gives nitrogen-doped TiO2 microspheres remarkably improved photocatalytic activity, compared with commercial mixed-phase TiO2 (P25) and single-phase anatase-type TiO2 . Furthermore, nitrogen-doped TiO2 microspheres display reliable photocatalytic performance for multiple cycles. The as-prepared nitrogen-doped TiO2 microspheres hold promise as efficient photocatalysts for various photocatalytic applications.